Whole-gland high-intensity focused ultrasound ablation and transurethral resection of the prostate in the patients with prostate cancer: A systematic review and meta-analysis - Pan, Yang; Wang, Shangren; Liu, Li; Liu, Xiaoqiang (Frontiers in Oncology, 2022)
Background We aimed to conduct a systematic review and meta-analysis of studies reporting functional and oncologic outcomes of combining whole-gland high-intensity focused ultrasound ablation (HIFU) with transurethral resection of the prostate (TURP) in prostate cancer (PCa) patients. Methods PubMed, Embase, Web of Science, Scopus, and Cochrane Library were systematically searched until June 30, 2022. The ROBINS-I tool scale was used to evaluate quality of eligible studies. Biochemical failure was defined according to the criteria used in each raw study. The presence of any cancer on follow-up biopsy was classified as “positive biopsy”. Patients able to penetrate their partner without pharmacologic support were rated potent. Meta-analysis was performed to evaluate functional outcomes using R project. Results A total of 1861 patients in 15 eligible studies were included. All studies were identified as moderate or high quality. There were 1388 (74.6%) patients with low-risk or intermediate-risk PCa in 15 studies and 473 (25.4%) patients with high-risk PCa in 12 studies. The mean PSA nadir postoperatively ranged from 0.20 to 1.90 ng/mL within average time of 1.9-12 months. Biochemical failure rates in all 15 studies ranged from 6.3% to 34% within average time of 1.9-60 months. Eleven studies reported the rates of positive biopsy ranged from 3% to 29.7% within average time of 3-12 months postoperatively. Based on the results of single-arm meta-analysis, the pooled rates of any degree urinary incontinence, acute urinary retention, urinary tract infections, and urethral stricture were 9.4% (95% CI: 6.1%-12.6%), 0.9% (95% CI: 0%-2%), 2.6% (95% CI: 0.8%-4.3%), and 4.3% (95% CI: 1.4%-7.1%), respectively. The pooled rate of being potent after procedure in previously potent patients was 43.6% (95% CI: 27.3%-59.8%). The sensitivity analysis revealed all the pooled results was relatively reliable. Egger’s tests for the pooled results of acute urinary retention (p = 0.0651) and potency (p = 0.6749) both did not show significant publication bias. Conclusions It appears that the combination treatment of whole-gland HIFU and TURP could be applied for PCa patients. It might have potential advantages of decreasing catheterization time and improving urinary status. Prospective and comparative studies are needed to validate our findings.